2014
DOI: 10.5194/amt-7-4203-2014
|View full text |Cite
|
Sign up to set email alerts
|

Liquid water absorption and scattering effects in DOAS retrievals over oceans

Abstract: Abstract. Spectral effects of liquid water are present in absorption (differential optical absorption spectroscopy -DOAS) measurements above the ocean and, if insufficiently removed, may interfere with trace gas absorptions, leading to wrong results. Currently available literature cross sections of liquid water absorption are provided in coarser resolution than DOAS applications require, and vibrational Raman scattering (VRS) is mostly not considered, or is compensated for using simulated pseudo cross sections… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 54 publications
1
39
0
Order By: Relevance
“…The influence of vibrational Raman scattering (VRS) of N 2 and O 2 as described in Lampel et al (2015) on the obtained results listed in Table 5 was not found to be significant. As also described in Lampel et al (2015), no significant contribution to observed ODs by VRS of liquid water (Vountas et al, 2003;Peters et al, 2014) was found most likely due to turbid water and consequently short light paths under water. VRS of water vapour itself is expected to result in an intensity offset and in differential structures especially at 459 and 463 nm, as it red shifts the solar spectrum by ≈ 3654cm −1 (Penney and Lapp, 1976;Murphy, 1978;Rizi et al, 2004).…”
Section: Max-doas Measurementsmentioning
confidence: 52%
“…The influence of vibrational Raman scattering (VRS) of N 2 and O 2 as described in Lampel et al (2015) on the obtained results listed in Table 5 was not found to be significant. As also described in Lampel et al (2015), no significant contribution to observed ODs by VRS of liquid water (Vountas et al, 2003;Peters et al, 2014) was found most likely due to turbid water and consequently short light paths under water. VRS of water vapour itself is expected to result in an intensity offset and in differential structures especially at 459 and 463 nm, as it red shifts the solar spectrum by ≈ 3654cm −1 (Penney and Lapp, 1976;Murphy, 1978;Rizi et al, 2004).…”
Section: Max-doas Measurementsmentioning
confidence: 52%
“…While the reference sector binning method used in this work will ensure that the geometric path length is near-identical in both cases, differences in the light paths caused by factors such as cloud cover and aerosol loading will need to be explicitly accounted for. The impact of vibrational Raman scattering on the DOAS fit (VRS, Peters et al, 2014) will also need to be accounted for, as the reference spectra is primarily measured over the Pacific Ocean. Accounting for these effects may further improve the ERrs-DOAS performance.…”
Section: Discussionmentioning
confidence: 99%
“…inside the spectrometer) which produces an intensity offset, also called stray light. In addition, other effects such as changes in the dark current can lead to intensity offsets and the vibrational Raman scattering (VRS) is known to produce spectral effects that are very similar to intensity offsets (Peters et al, 2014;Lampel et al, 2015). In the DOAS fit, pseudo cross sections are usually included in order to compensate for intensity offsets.…”
Section: Intensity Offset Correctionmentioning
confidence: 99%